Working Together for a Rich Assessment Program for Students Student’s Assessment; a Possibility for Teachers’ Professional Growth - Mezini, Edlira Sina (Richtmann Publishing, 2012)
Educators, curriculum specialists are emphasizing that teaching goals must encourage to students skills such as criticalthinking, reasearch, and problem-solving. Student’s assessment is an integral part of instruction (teaching) process which gives studentsthe chance to express freely their thoughts, ideas; to reason and take part actively expressing their abilities and skills during the teachingprocess. Skills and knowledge can be acquired through a teacher-student cooperation aiming to achieve a final goal.